THE UTILIZATION OF EDMODO PLATFORMS IN ENGLISH LEARNING - Lisa Fitri Meidipa; Yulia Rizki Ramadhani; Nursaima Harahap (Institut Pendidikan Tapanuli Selatan, 2021)
The utilization of information technology as a learning media to support the learning process in schools is essential. Furthermore, efforts are needed to realize a learning process that uses effective learning methods according to the expectations of the Government. Especially in the current era, the spread of the coronavirus is still high, making online learning platforms one of the alternatives so that education can continue to run. The risk of being exposed to the virus can be avoided. Moreover, one of the online learning platforms that can be used is Edmodo. Not only communicating through this platform, but teachers can also learn by sharing content in the form of text or videos, practice questions, and homework (PR). This study uses a quantitative approach. The method used in this research is quasi-experimental. This research was conducted on class X SMA Negeri 2 Padangsidimpuan. The results showed that through the application of the Edmodo platform in learning English online, there was a significant effect between the pretest and posttest. Based on the analysis test results through the t-test, the significance value stated that it was smaller than 0.05. So, Ha was accepted, which means that the pretest and posttest results experienced significant changes (meaning/influential).